Hubungan Nilai Laju Endap Darah (LED) dengan Kadar C-Reactive Protein (C-RP) pada Pasien Positif Covid-19 - Tsamarah, Yumna Tahani; Danuyanti, I Gusti Ayu Nyoman; Zaetun, Siti (Faculty of Medicine, Universitas Andalas, 2021)
SARS-CoV-2 infection is a systemic infection that significantly affects hematopoiesis and the patient's immune response. Drastic increase in the production of proinflammatory cytokines like interleukin-6 (IL-6) play a role in mechanism of lymphopenia in COVID-19. Some indicators of inflammation markers include Erythrocyte Sedimentation Rate (ESR) and C-Reactive Protein (CRP). Objectives: To determined the correlation between Erythrocyte sedimentation rate (ESR) and C-Reactive Protein (C-RP) levels in patients with covid-19. Methods: This research was an analytic observational study with a cross-sectional approach. The samples in this research were 10 ESR and 10 CRP data in a patient with positive COVID-19 at the Mataram University Hospital. Results: A minimum value of 0.50 was obtained from 10 samples of CRP examination, while the maximum value was 79.90 with an average value of 32.24 and a standard deviation of 30.36. The Erythrocyte sedimentation rate (ESR) examination obtained a minimum value of 6.00 from 10 samples, while the maximum value was 103.00 with an average value of 53.60 and a standard deviation of 36.40. Conclusion: There is no correlation between the value of Erythrocyte sedimentation rate and C-Reactive Protein levels in patients with Covid-19.Keywords: Covid-19, C-reactive protein, erythrocyte sedimentation rate